Cu2SnS3 Inorganic-Organic Hybrid Structures for Photovoltaic Applications. Issue 1784 (25th June 2015) - Dias, Sandra; Krupanidhi, S. B.
ABSTRACT: We report the synthesis of Cu2 SnS3 (CTS) nanostructures and its incorporation into an inorganic-organic hybrid device to enhance the photoresponse under AM 1.5 G solar illumination. The nanostructures were structurally and optically characterized. From X-ray diffraction (XRD) and Transmission electron microscopy (TEM) the CTS nanocrystals were found to be tetragonal. Flower like structures of CTS were obtained as seen from Scanning electron microscopy (SEM). A band gap of 1.4 eV was obtained from absorption studies. Two devices have been studied, P3HT: PCBM = 1: 1 and CTS: P3HT: PCBM = 8:1:1. The photocurrent increased from a value of 2.33 mA at dark to 2.5 mA for the P3HT-PCBM blend to 3.36 mA for CTS: P3HT: PCBM = 8:1:1 device. The responsivity, sensitivity, external quantum efficiency and specific detectivity increased from 18.81 mA/W, 1.07, 4.25% and 6.88 × 10 8 Jones respectively for P3HT:PCBM sample to 189.97 mA/W, 1.44, 42.9% and 6.95 × 10 9 Jones for CTS: P3HT: PCBM = 8:1:1 sample at 1V bias and 1 Sun illumination intensity. The time dependent photoresponse was stable over different ON-OFF cycles. From the fit to the rise and decay curves, the rise and decay time constants were obtained.